Inheritance Rights of Inactive Digital Accounts: Qiyās-Based Legal Protection - Mayasari, Lutfiana; Triyono, Nur; Wulan Agustina, Ulfa; Mukti, Beta Pujangga (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2023)
In this digital world, the death of a person may create issues concerning the deceased’s digital accounts. While the rights of the account holder remain with the account holder while alive, most providers do not allow transfers if the account becomes inactive or the holder dies. In the Indonesian context, 207 million users are exposed to the risk of losing their rights to digital accounts. This research explores the entitlements linked to virtual account ownership and legal protections for the inheritable rights of inactive account holders through qiyās method. Employing a conceptual, legal, and philosophical approach, the study reveals various entitlements connected to the account owner. The owners of an inactive account possess the right, and therefore, it can be inherited. Legal safeguards for inactive digital account owners are present through argument and qiyās (analogy) to ensure their rights as heirs and enable inactive digital account assets to be inherited as non-digital assets. At this point, it is essential to explore the inheritance rights of digital assets further by studying positive law and Islamic law to guarantee personal rights in the digital space.